What does the past mean for the future? A meta-analysis of perceived organizational support in hospitality and tourism - Yan, Zhen; Zhang, Zongguo; Choo, Wei Chong (Elsevier, 2024)
Although a large number of empirical studies on the outcomes of perceived organizational support (POS) have been conducted in the hospitality and tourism context, no research has provided a holistic understanding of POS in this field. This paper aims to meta-analyze POS and examine various moderating variables based on 81 articles (19 outcomes, N = 26,532). The results suggest that POS has different effects on outcomes including job attitudes, emotional labor, role conflicts and facilitation, stress at workplace, service perception, performance and behaviors and intention to leave. The results also show that national culture, measurement and time lag significantly moderate the relationships between POS and its outcomes. POS holds a robust level of validity for explaining outcomes related to job attitudes, behaviors and service perception within the hospitality and tourism domain. In light of this, an extensive body of research has been dedicated to investigating the associations between POS and attitudinal as well as behavioral outcomes. As such, it becomes apparent that the repetitive application of identical frameworks to examine the impact of POS may be less imperative. Rather, forthcoming research on POS is anticipated to incorporate cultural and methodological determinants. To our knowledge, this paper is the first attempt to propose and test a framework of outcomes of POS in the domain of hospitality and tourism with a quantitative meta-analytic method. Furthermore, the current study adds value by examining various moderators, which has not been done in previous review articles of POS. It also provides future research directions for POS. © 2024 The Authors